The Influence of Substituting Prices, Product Returns, and Service Quality on Repurchase Intention. (27th November 2021) - Xue, Jian; Rasool, Zeeshan; Khan, Mohsin Ali; Khan, Ahmad Imran; Khan, Farooq; Khan, Anum Afzal; Shoukat, Rabail; Ali, Hina
Abstract : The textile industry is production-intensive and incorporates diverse transactions made by multiple suppliers, corporate buyers, and supply chain members. In the business-to-business context, the cost for attracting a new customer is notably much higher than that needed to retain a present one. Customer loyalty in terms of customer repurchase intention has, therefore, been considered as a key determinant for textile companies to improve their efficiency and competitive advantage. This study aims to investigate the business-to-business repurchase intentions of Pakistan textile and clothing industry customers. The study framework specifically consolidates the mutual dynamics of appealing (service quality), facilitating (product returns), and averting (switching costs) factors altogether and the effect of these variables on customer satisfaction and thus on customer retention (repurchase intent) in the textile's transactional scenario. A sample survey method is used for this study. The data collected through self-administered questionnaires ( n = 325) from All Pakistan Textile Mills Association enlisted the employees of the companies. The structural equational modeling technique was applied to examine the study hypotheses. The findings contended that service quality and switching costs are essential determinants that shape the repurchase intentions. Therefore, product returns do not contribute toward customer satisfaction and also do not shape the intentions of business-to-business customers to repurchase from the same supplier after having even a good product return experience in past.